Transportation A Global Supply Chain Perspective - Novack, Robert A.; Gibson, Brian J.; Suzuki, Yoshinori (Cengage, 2024)
Gain a solid understanding of what is arguably the most critical and complex component of global supply chains with Novack/Gibson/Suzuki's TRANSPORTATION: A GLOBAL SUPPLY CHAIN PERSPECTIVE, 10E. You learn the fundamental role and importance of transportation in companies and society as you study the current complex environment of transportation service. The authors introduce the role of transportation in supply chains and provide an overview of the operating and service characteristics, cost structure and challenges that today's transportation providers face. Updates throughout this edition highlight critical transportation management issues with insights into the strategic activities and challenges in the movement of goods through the supply chain. You examine global topics with the latest coverage of hard and soft technology and interesting discussions of fuel, energy, managerial, economic and environmental issues.